PENGARUH PENDEKATAN SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) BERBANTUAN MEDIA SCRAPBOX TERHADAP KEMAMPUAN LITERASI SAINS PESERTA DIDIK SEKOLAH DASAR - Qomariyah, Afifah Nur Amatullah; Iskandar, Sofyan; Nuraeni, Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the problem of low literacy skills of students. The low level of scientific literacy has an impact on the lack of understanding of science concepts, students' difficulties in implementing science and technology in everyday life, and students' lack of awareness of surrounding issues, such as the environment, health, economy, and even social problems. The cause is due to lack of information on extensive learning resources, inappropriate approaches and methods used in the learning process, inadequate facilities and infrastructure, and learning media, and learning that is not based on problems in everyday life. The purpose of this study was to determine the effect of using scrapbook media on the scientific literacy skills of fifth grade students of SDN Palasari 01, Cileungsi District, Bogor Regency. The method used in this study was a quantitative experimental method with a quasi-experimental design of the non equivalent group design type. There was a positive effect of the STEM (Science, Technology, Engineering, and Mathematics) approach assisted by scrapbox media on the scientific literacy skills of elementary school students. The results of this study state that there is a positive influence of the STEM (Science, Technology, Engineering, and Mathematics) approach assisted by scrapbox media on the scientific literacy skills of elementary school students. Keywords: learning media, science literacy, STEM approach